Práticas e sentidos das cooperativas de trabalho: um estudo a partir da economia solidária - Anjos, Eliene Gomes dos (Universidade do Vale do Rio dos Sinos, 2012)
In the present study, we investigated the labor cooperatives of solidarity economy. The aim of the sudy was to examine the labor relations and the meaning that labor takes, in order to assess to what extent and under what conditions the practices and meanings represent effective advances toward workers emancipation. To that end, we relied on quantitative research with data from the first nationwide mapping of solidarity economy enterprises, conducted between 2005 and 2007, and on qualitative research based on direct observation in the circles of solidarity economy, as well as four case studies. From the database subset consisting exclusively of cooperatives that claimed to have members working in the enterprise and to undertake collective production or rendering of services, we had data of 1257 cooperatives available for analysis. This step of the investigation revealed that those cooperatives face countless hardships to achieve such economic performance as to guarantee the workers social rights, and are limited, in most cases, to paying their workers on the basis of productivity or hours worked. On the other hand, we found that the cooperatives have widened the political participation of workers as they have been included in the spaces of political claims of solidarity economy and the demands surrounding it. The qualitative research, conducted in Salvador and during solidarity economy events, corroborated the picture drawn by the statistical data, thus contributing to demonstrate that the people involved in those experiences are mostly women, black individuals, workers with no or low professional qualification. In other words, we found that the associated workers come from segments of the population that have historically experienced processes of exclusion and were involved in informal occupations. In that context, solidarity economy labor cooperatives create a contradictory instance. While associated labor carries a sense of emancipation, since the workers take part in the decision-making process, manage the enterprises collectively and share their outcomes, it also promotes the intensification of that form of labor, which is marked by instability ? thus resembling precarious work. Nevertheless, the segments that contribute their workforce to those cooperatives accomplished advances in working conditions when compared with the forms of labor formerly exercised. As far as social rights are concerned, those cooperatives still have a long way to go, since they have not achieved economic viability to assure those rights. Therefore, the need for a new regulation is imperative in order to prevent precarious work and alienation from social protection ? a situation often encountered in the occupational paths of those who currently resort to selfmanagement to ensure their reproduction.
Keywords: Cooperativas de trabalho; Economia solidária; Trabalho associado; Emancipação social; Processo de informalidade; Labor cooperatives; Solidarity economy; Associated labor; Social emancipation; Informal process; ACCNPQ::Ciências Humanas::Sociologia